Utility of brain fluorodeoxyglucose PET in children with possible autoimmune encephalitis - Aydos, Uğuray; Arhan, Ebru; Akdemir, Ümit Özgür; Akbaş, Yılmaz; Aydın, Kürşad; Atay, Lütfiye Özlem; Serdaroğlu, Ayşe (Lippincott Williams & Wilkins, 2020)
Purpose We aimed to explore the utility and additional clinical contribution of brain fluorodeoxyglucose (FDG) PET imaging for the assessment of children with possible autoimmune encephalitis in comparison to brain MRI. Materials and methods We conducted a retrospective analysis of six pediatric patients (all seronegative) between 2014 and 2019 with the initial diagnosis of possible autoimmune encephalitis who had brain FDG PET/CT or PET/MRI and brain MRI during the diagnostic period. Diagnosis of possible autoimmune encephalitis was based on clinical consensus criteria defined by Grauset al. Brain FDG PET images were visually evaluated. Semiquantitative evaluation was also performed by using the statistical parametric mapping (SPM) method. Results Cerebrospinal fluid pleiocytosis and electroencephalography abnormality were present in all patients. Mean duration between the onset of symptoms and brain FDG PET imaging was 33 +/- 16 days (range: 18-62 days). There were a total of eight brain FDG PET scans (six of PET/MRI and two of PET/CT). In two patients, FDG PET imaging was performed at diagnosis and follow-up. Initial FDG PET and SPM analysis findings were abnormal in all patients (100%), with four demonstrating only hypometabolism. Only a hypermetabolic pattern was seen in one patient, and mixed the hypohypermetabolic pattern was seen in one patient. All patients had metabolic abnormalities in temporal lobes. Additionally, visual and semiquantitative FDG PET findings revealed hypometabolism in extratemporal regions. Brain MRI was abnormal in two patients (33.3%) who had also FDG hypermetabolism in mesial temporal lobes. Conclusions Our findings support the usage of fluorine-18-FDG PET/computed tomography (CT)/MRI with quantitative analysis early in the diagnostic work-up of possible autoimmune encephalitis, particularly in those with normal or nonspecific MRI findings. However, it remains a purpose of further studies, if and to what extent FDG PET/CT or integrated FDG PET/MRI with quantitative analysis can improve the diagnostic workup of children with possible autoimmune encephalitis.
Keywords: Autoimmune Encephalitis; Brain Fluorodeoxyglucose PET; Children; PET; Computed Tomography; MRI